ta có:
[tex]A = \frac{10^{20}+1}{10^{19}+1}[/tex]
=> [tex]\frac{1}{10}A = \frac{10^{20}+1}{10^{20}+ 10}[/tex]
= [tex]\frac{10^{20}+10-9}{10^{20}+10}[/tex]
= [tex]1 - \frac{9}{10^{20}+10}[/tex]
ta lại có:
[tex]B= \frac{10^{21}+1}{10^{20}+1}[/tex]
=> [tex]\frac{1}{10}B= \frac{10^{21}+1}{10^{21}+ 10}[/tex]
= [tex]\frac{10^{21}+10-9}{10^{21}+10}[/tex]
= [tex]1 - \frac{9}{10^{21}+10}[/tex]
Vì [tex]10^{20}+10< 10^{21}+10[/tex]
=> [tex]\frac{1}{10^{20}+10}> \frac{1}{10^{21}+10}[/tex]
=> 1 - [tex]\frac{9}{10^{20}+10}< 1-\frac{9}{10^{21}+10}[/tex]
=> [tex]\frac{1}{10}A <\frac{1}{10}B[/tex]
=> A < B.